Promoção da saúde na unidade de terapia intensiva: Influência dos fluxos respiratórios sobre a incidência de pneumonia associada à ventilação mecânica - Salge, Juliana Almeida de Souza Borges (2013)
Ventilator-associated pneumonia (VAP) is the most frequent nosocomial infection in the intensive care unit (ICU). VAP prolongs the duration of mechanical ventilation (MV) and hospital stay, and increases the mortality. In this way the PAV can be understood with the determining factor in the decrease of quality of life. Since the late 1980 there is increased evidence that adjustments in ventilator can produce a flow bias that may clear or embed mucus during MV. The ratio between the peak inspiratory flow (PIF) and the peak expiratory flow (PEF), or the difference between both, are described as possible critical factors that may influence the movement of secretion. To investigate in mechanically ventilated patients the effect of flow bias on the incidence of VAP. Participated in the study patients under MV for less than 24 h and which were expected to continue under MV for more than 72 h. The exclusion criteria were: suspicion of pneumonia prior to MV; aspiration during intubation; and severe hypoxemia. Respiratory mechanics were registered at the time of entering in the study and every each 12 h during the first 60 h using CO2SMO® monitor. VAP diagnostic was made based on new or worsening radiographic infiltrates and leukocytosis or leucopenia, fever or purulent sputum. Total time of MV, ICU and time of hospital stay were registered. Patients that developed VAP were classified as VAP group and patients that did not presented VAP as control group. Statistical analyses were performed using the unpaired t-test and a two-way analysis for repeated measures as appropriate. Although the differences were not significant, the VAP group compared to the control group was older and had a slightly higher APACHE score. Total time of MV, ICU and time of hospital stay were significantly higher in the VAP group compared to the control. There were no differences between the PIF/PEF ratio (p=0,080) and the PEF-PIF difference (p=0,110) during the first 60 h of MV between the two groups. The mean±SE PIF/PEF ratio and PEF-PIF difference were in the VAP group 1,5±0,5 and -14,1±1,5 and in the control 1,6 ± 0,7 and -17,5±1,4, respectively. These results of a current study suggest that an inspiratory flow bias during the first 60h of MV does not influence the incidence of VAP. Both groups, VAP and control, were ventilated with a PIF/PFE ratio much higher than the threshold described in the literature - PIF/PFE ratio > 0,9 - which, theoretically, is sufficient to move mucus towards the lungs. The negative mean PEF-PIF differences in both groups also indicated that secretion was moved deeper into the lungs. As expected, patients with VAP had longer time of MV, ICU and hospital length.